Hydroxycinnamic acid amide metabolism: physiology and biochemistry - Facchini, P.J.; Hagel, J.; Zulak, K.G.
Hydroxycinnamic acid amides (HCAAs)are a widely distributed group of plant secondary metabolites purported to function in several growth and developmental processes including floral induction, flower formation, sexual differentiation, tuberization, cell division, and cytomorphogenesis. Although most of these putative physiological roles for HCAAs remain controversial, the biosynthesis of amides and their subsequent olymerization in the plant cell wall are generally accepted as integral components of plant defense responses to pathogen challenge and wounding. Tyramine-derived HCAAs are commonly associated with the cell wall of tissues near pathogen-infected or woundhealing regions. Moreover, feruloyltyramine and feruloyloctapamine are covalent cell wall constituents of both natural and wound periderms of potato (Solanum tuberosum)tubers, and are putative components of the aromatic domain of suberin. The deposition of HCAAs is thought to create a barrier against pathogens by reducing cell wall digestibility. HCAAs are formed by the condensation of hydroxycinnamoyl-CoA thioesters with phenylethylamines such as tyramine, or polyamines such as putrescine. The ultimate step in tyramine-derived HCAA biosynthesis is catalyzed by hydroxycinnamoyl- CoA:tyramine N-(hydroxycinnamoyl)transferase (THT; E.C. 2.3.1.110). The enzyme has been isolated and purified from a variety of plants, and the corresponding cDNAs cloned from potato, tobacco (Nicotiana tabacum), and pepper (Capsicum annuum). THT exhibits homology with mammalian spermidine-spermine acetyltransferases and putative N-acetyltransferases from microorganisms. In this review, recent advances in our understanding of the physiology and biochemistry of HCAA biosynthesis in plants are discussed.